2013
DOI: 10.1016/j.msec.2013.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Patterned carbon nanotubes as a new three-dimensional scaffold for mesenchymal stem cells

Abstract: We investigated the cellular adhesive features of mesenchymal stem cells (MSC) on non-coated and collagen coated patterned and vertically aligned carbon nanotube (CNT) structures mimicking the natural extra cellular matrix (ECM). Patterning was achieved using the elasto-capillary induced by water treatment on the CNT arrays. After confirmation with specific markers both at transcript and protein levels, MSCs from different passages were seeded on either collagen coated or non-coated patterned CNTs. Adhesion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…1b). The average width of these cavities was 10 m. The mechanism behind the formation of selfassembled patterning is based on the elasto-capillary effect and hydrophobic property of aligned CNTs as explained by us and others previously [18,30]. Our experimental design of patterning was shown in Fig.…”
Section: Preparation Of Va-cntsmentioning
confidence: 94%
See 4 more Smart Citations
“…1b). The average width of these cavities was 10 m. The mechanism behind the formation of selfassembled patterning is based on the elasto-capillary effect and hydrophobic property of aligned CNTs as explained by us and others previously [18,30]. Our experimental design of patterning was shown in Fig.…”
Section: Preparation Of Va-cntsmentioning
confidence: 94%
“…VA-CNTs were synthesized through ACCVD method on Si substrates using sandwich catalyst design (Al/Co/Al) as we reported previously [18]. The side view SEM image of VA-CNTs revealed that CNTs were 10 m in height whereas their average diameters were around 10 nm shown by TEM analysis (Fig.…”
Section: Preparation Of Va-cntsmentioning
confidence: 99%
See 3 more Smart Citations